Dendritic Cells in Dengue Virus Infection: Targets of Virus Replication and Mediators of Immunity - Schmid, Michael A.; Diamond, Michael S.; Harris, Eva (Frontiers in Immunology, 2014)
Dendritic cells (DCs) are sentinels of the immune system and detect pathogens at sites of entry, such as the skin. In addition to the ability of DCs to control infections directly via their innate immune functions, DCs help to prime adaptive B and T cell responses via antigen presentation in lymphoid tissues. Infected Aedes aegypti or Ae. albopictus mosquitoes transmit the four dengue virus (DENV) serotypes to humans while probing for small blood vessels in the skin. DENV causes the most prevalent arthropod-borne viral disease in humans, yet no vaccine or specific therapeutic is currently approved. Although primary DENV infection confers life-long protective immunity against re-infection with the same DENV serotype, secondary infection with a different DENV serotype can lead to increased disease severity via cross-reactive T cells or enhancing antibodies. This review summarizes recent findings in humans and animal models about DENV infection of DCs, monocytes and macrophages. We discuss the dual role of DCs as both targets of DENV replication and mediators of innate and adaptive immunity, and summarize immune evasion strategies whereby DENV impairs the function of infected DCs. We suggest that DCs play a key role in priming DENV-specific neutralizing or potentially harmful memory B and T cell responses, and that future DC-directed therapies may help induce protective memory responses and reduce dengue pathogenesis.